Short Communication: Rediscovery of a remnant habitat of the critically endangered species, Hopea sangal, in Pasuruan District, East Java, Indonesia - SOEJONO SOEJONO (Society for Indonesian Biodiversity, 2014)
Soejono. 2014. Rediscovery of a remnant habitat of the critically endangered species, Hopea sangal, in Pasuruan District, East Java, Indonesia. Biodiversitas 15: 236-239. During recent exploration for surviving indigenous flora carried out in Pasuruan District, EastJava, the endangered tree species, Hopea sangal Korth., has been rediscovered in a previously unknown location in East Java. TheIUCN Red List of Threatened Species, 2012, stated that H. sangal is critically endangered, A1cd, B1+2c, C1, D ver 2.3. This discoveryof H. sangal, and other supporting species that may still survive, can support the program of recovery of threatened plant species. At least for Pasuruan region, the remaining habitat, can be used as the core for H. sangal protection, thus H. sangal can breed naturally and sustainably. This information also can be used as one of the references or consideration tools for stakeholders to determine the priority of restoration policy.